The Current Status and Future of the Education Sector in Homoeopathy (Homoeopathy for All, 2025)
Homeopathy was founded 200 years  ago by Dr. Samuel Hahnemann who  gave direction to this branch of  medicine with his famous concept  “similia similibus curentur” (‘let  like cure likes’). Homeopathy is  based on three basic principles: 1. The rule of similia  2. Testing of medicament in  healthy human being  3. The principle of homeopathic  doses. Homoeopathy, has evolved into  a globally recognized modality,  particularly in countries such as India,  Germany, Brazil, and the UK. The  education sector in homoeopathy has  seen remarkable development over  the last few decades, particularly  with state-sanctioned institutional  frameworks and integration into  public healthcare systems. However,  the field also faces substantial  challenges, including issues of  scientific validation, curriculum  reform, global acceptance, and  integration with mainstream  medicine. This article provides a  critical and detailed analysis of  the current status of homoeopathic  education and proposes strategic  pathways for its future development
Keywords: globally recognized; alignment; interventions; purview